Use of additional biomarkers in the assessment of the impact of food based zinc interventions on zinc status in adults - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A systematic review on the diagnostic performance of FADS1 and FADS2 and the state of readiness of these potential biomarkers for monitoring and evaluation of zinc interventions was completed, but will not be published before the end of A4NH. For context, a link to the consultation report is provided.